Electromagnetic waves transmission performance of alumina refractory ceramics in 2.45 GHz microwave heating. Issue 17 (1st December 2019) - Shang, Xiaobiao; Zhai, Di; Zhang, Fucheng; Wei, Cong; Chen, Junruo; Liu, Meihong; Peng, Jinhui
Abstract: Refractory materials are an important part of industrial microwave heating equipment, and their transmission performance has a significant influence on the efficiency and uniformity of microwave heating. In this study, electromagnetic wave power transmission coefficients (PTCs) of alumina refractory ceramics are calculated within the temperature range of 22–1379 °C and the thickness range of 0–0.1 m at 2.45 GHz, and the influences of the complex dielectric constant of the material, the thickness of the medium, the polarisation mode of the electromagnetic waves, and the incident angle of the electromagnetic waves on PTC are analysed. It was found that the transmission performance of alumina ceramics fluctuates with increasing thickness at different temperatures and that there are several transmission peaks. The transmission performance in a transverse electric (TE) field decreases monotonically with increasing incident angle, and the PTC is equal to zero when the incident angle is 90°. The transmission performance in a transverse magnetic (TM) field increases first and then decreases with increasing incident angle, and there is a transmission peak. Transmission peaks at different thicknesses form a 'ridge' at the Brewster's angle, at which the fluctuation amplitude of PTC becomes very small. As the temperature increases, the 'ridge' becomes steeper. Finally, the incident angle range with good transmission performance of alumina ceramics in the temperature range of 22–1379 °C is obtained, and the optimal thickness interval at the optimum incident angle (73.8°) is calculated for reference. This research has important guiding significance for the selection and optimisation of refractory ceramic materials for use in microwave high-temperature heating.